Micro-expansion layer spherical graphite and preparation method thereof
By performing micro-layer expansion treatment on spherical graphite with acidification, hydrolysis, filtration and sintering, the problem of volume expansion and contraction of spherical graphite in lithium-ion batteries during charging and discharging is solved, and the battery performance is improved.
Patent Information
- Application Number
- CN202411847748.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing spherical graphite is prone to volume expansion and contraction during charging and discharging of lithium-ion batteries, resulting in peeling and powdering of graphite sheets, thereby reducing battery electrical performance.
The spherical graphite is micro-expanded through steps such as acidification, hydrolysis, filtration and sintering, increasing its layer spacing and controlling the tap density, particle size and specific surface area to ensure the optimization of electrochemical performance.
On the basis of maintaining the consistency of other physical properties, the layer spacing of the micro-expanded spherical graphite expanded to 0.335-0.450nm, and the tap density was ≥0.5g/ml, which significantly improved the rate performance and cycling performance of lithium-ion batteries.
Smart Images

Figure CN119461357A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of negative electrode materials for lithium ion batteries, and specifically relates to micro-expanded layer spherical graphite and a preparation method thereof. Background Art
[0002] Spherical graphite is often used as a negative electrode material for lithium-ion batteries because of its suitable relevant physical properties (specific surface area, tap density, particle size, etc.). However, the bonding force between graphite layers is mainly van der Waals force. During charging and discharging, lithium ions will cause the volume of spherical graphite to expand and shrink during the intercalation and deintercalation process, and it is easy for the graphite sheets to peel off and pulverize, resulting in poor electrical performance of lithium-ion batteries.
[0003] Micro-expansion of spherical graphite is one of the commonly used methods of graphite modification. However, in the process of modifying spherical graphite using relevant chemical methods, other intrinsic properties other than the interlayer spacing of spherical graphite are often changed. How to ensure the consistency of other physical properties while micro-expanding the spherical graphite is a problem that R&D personnel need to solve. Summary of the invention
[0004] The first purpose of the present invention is to provide a method for preparing micro-expanded spherical graphite, comprising the following steps: acidifying, hydrolyzing, filtering and sintering the spherical graphite, wherein the interlayer spacing of the micro-expanded spherical graphite is greater than the interlayer spacing of the spherical graphite.
[0005] In some embodiments of the first object of the present invention, the acidification comprises mixing the spherical graphite with sulfuric acid, wherein the concentration of the sulfuric acid is ≥ 90%.
[0006] In some embodiments of the first object of the present invention, the mass ratio of spherical graphite to sulfuric acid is 1:40-50.
[0007] In some embodiments of the first aspect of the present invention, the hydrolysis comprises directly adding water to the acidified spherical graphite to replace the interlayer acid of the spherical graphite.
[0008] In some embodiments of the first object of the present invention, the sintering includes a carbonization treatment at 900-1400° C., and the carbonization treatment time is 16-24 hours.
[0009] In some embodiments of the first object of the present invention, the filter pressing includes mixing the hydrolyzed spherical graphite with water and ammonia water, and filter pressing the mixture into a solid state.
[0010] In some embodiments of the first object of the present invention, during the filter pressing step, the mass ratio of ammonia water to spherical graphite is 1:1-10; Preferably, the mass ratio of spherical graphite to water in the filter press process is 1:40-50; Preferably, the reaction time of the filter press process is 20 to 28 hours.
[0011] The second object of the present invention is to provide a micro-expanded spherical graphite, which is prepared by the preparation method provided by the first object of the present invention, and the interlayer spacing of the micro-expanded spherical graphite is 0.335-0.450nm, and the tap density is ≥0.5g / ml.
[0012] In some embodiments of the second object of the present invention, the particle size of the micro-expanded spherical graphite is 10-20 μm, and / or the specific surface area is 5-12 m 2 / g.
[0013] In some embodiments of the second object of the present invention, the interlayer spacing of the micro-expanded spherical graphite is 0.335-0.450 nm, the tap density is ≥0.5 g / ml, and the sulfur content is ≤50 ppm.
[0014] The beneficial effect of the present application is that while the spherical graphite is micro-expanded, its other physical properties, such as tap density, particle size, and specific surface area, are still within a reasonable range, and are basically indistinguishable from the intrinsic properties of spherical graphite. In addition, no impurity elements are introduced during the preparation process, thereby ensuring the electrochemical properties of the micro-expanded modified spherical graphite. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a particle size test diagram of spherical graphite raw materials; Figure 2 This is the SEM electron microscope image of spherical graphite raw material; Figure 3 This is a particle size test diagram of the micro-expanded layer spherical graphite obtained in Example 1; Figure 4 This is the SEM electron microscope image of the micro-expanded layer spherical graphite obtained in Example 1; Figure 5 This is a particle size test diagram of the modified spherical graphite obtained in Comparative Example 1; Figure 6 This is the SEM electron microscope image of the modified spherical graphite obtained in Comparative Example 1; Figure 7 This is a particle size test diagram of the modified spherical graphite obtained in Comparative Example 2; Figure 8 This is the SEM electron microscope image of the modified spherical graphite obtained in Comparative Example 2; Fig. 9 This is a particle size test diagram of the modified spherical graphite obtained in Comparative Example 3; Fig.10 This is the SEM electron microscope image of the modified spherical graphite obtained in Comparative Example 3. DETAILED DESCRIPTION
[0016] The following detailed description of exemplary embodiments of the present invention refers to the accompanying drawings, which form a part of the description, in which exemplary embodiments of the present invention are shown as examples, wherein the features of the present invention are identified by reference numerals. The following more detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but is merely for illustration and does not limit the description of the features and characteristics of the present invention, in order to propose the best way to perform the present invention, and is sufficient to enable those skilled in the art to implement the present invention. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description and the accompanying drawings should be considered only as illustrative, not restrictive, and if there are any such modifications and variations, they will all fall within the scope of the present invention described herein. In addition, the background technology is intended to illustrate the current status and significance of the research and development of the present technology, and is not intended to limit the present invention or the application field of the present application and the present invention.
[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.
[0018] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0019] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0020] During the research and development process, the applicant found that some physical properties of spherical graphite, such as specific surface area, tap density, particle size, etc., are very suitable for use as negative electrode materials for lithium-ion batteries in practice. However, the bonding force between graphite layers is mainly van der Waals force. During charging and discharging, lithium ions will cause the volume expansion and contraction of spherical graphite during the deintercalation process, and it is easy to peel and pulverize the graphite sheets, resulting in poor electrical performance of lithium-ion batteries. Micro-expansion of spherical graphite is a common practice to solve the above problems. In the existing technical means, many researchers will fully oxidize spherical graphite. Although high-degree oxidation expands the interlayer spacing, physical parameters such as specific surface area and tap density will also be affected. At the same time, impurity elements are easily introduced during the oxidation process to affect the electrochemical properties of spherical graphite.
[0021] The first purpose of the present invention is to provide a method for preparing micro-expanded spherical graphite, comprising the following steps: acidifying, hydrolyzing, filtering and sintering the spherical graphite, wherein the interlayer spacing of the micro-expanded spherical graphite is greater than the interlayer spacing of the spherical graphite.
[0022] The use of strong acids such as sulfuric acid (H2SO4) or nitric acid (HNO3) can slightly expand the interlayer spacing of spherical graphite. This is because the acid removes some impurities and defects between the spherical graphite layers, and introduces new functional groups such as carboxyl (-COOH) or hydroxyl (-OH) between the layers. The introduction of these functional groups increases the interlayer force, resulting in a slight expansion of the interlayer spacing.
[0023] In some embodiments of the first aspect of the present invention, the concentration of sulfuric acid is ≥90%.
[0024] In some embodiments of the first object of the present invention, the mass ratio of spherical graphite to sulfuric acid is 1:40 to 50. If the amount of sulfuric acid used is small, the purpose of layer expansion cannot be achieved, and if the amount of sulfuric acid used is large, the layer expansion is excessive and the spherical graphite structure is destroyed.
[0025] In some embodiments of the first purpose of the present invention, the hydrolysis includes directly adding water to the acidified spherical graphite to replace the interlayer acid of the spherical graphite, thereby preventing the residual acid from continuously performing an expansion reaction on the spherical graphite; at the same time, no reducing agent is added to the acidified spherical graphite for oxidation reaction, and the micro-expansion of the spherical graphite is completed by relying solely on strong acid.
[0026] In some embodiments of the first object of the present invention, the sintering includes a carbonization treatment at 900-1400° C. for 16-24 hours. The carbon content of the product can be controlled by the carbonization treatment, thereby obtaining a product with a target carbon content.
[0027] In some embodiments of the first object of the present invention, the filter press includes mixing the hydrolyzed spherical graphite with water and ammonia water for reaction, and filter pressing it into a solid state. Since sulfuric acid is used in the micro-expansion of the spherical graphite, sulfur is introduced in this process. Sulfur may form a variety of lithium sulfides in the electrochemical process. These lithium sulfides have poor electrochemical stability and are easily dissolved in the electrolyte, resulting in rapid decay of the battery capacity. At the same time, the presence of sulfur may promote the decomposition of the electrolyte and produce insoluble solid by-products. These by-products will be deposited on the electrode surface, increase the internal resistance of the battery, and reduce the battery performance. In the filter press process, adding ammonia water can remove the sulfur remaining in the acidified spherical graphite, thereby achieving the purpose of controlling the sulfur content.
[0028] In some embodiments of the first purpose of the present invention, during the filter pressing step, the mass ratio of ammonia water to spherical graphite is 1:1~10; if the ammonia water content is too little, it will not fully remove sulfur, and if the ammonia water content is too high, new impurities may be introduced.
[0029] Preferably, the mass ratio of spherical graphite to water in the filter press process is 1:40-50; Preferably, the reaction time of the filter press process is 20 to 28 hours.
[0030] The second object of the present invention is to provide a micro-expanded spherical graphite, which is prepared by the preparation method provided by the first object of the present invention, and the interlayer spacing of the micro-expanded spherical graphite is 0.335-0.450nm, and the tap density is ≥0.5g / ml. The interlayer spacing of the spherical graphite is micro-expanded to 0.335-0.450nm, which can reasonably widen the lithium ion diffusion channel, improve the rate performance of the spherical graphite, and alleviate the volume expansion and contraction caused by the lithium ion insertion and extraction process, and improve the cycle performance; at the same time, the tap density is controlled to ≥0.5g / ml, which can ensure the energy density, thereby storing as much energy as possible.
[0031] In some embodiments of the second object of the present invention, the particle size of the micro-expanded spherical graphite is 10-20 μm, and / or the specific surface area is 5-12 m 2 / g.
[0032] The appropriate particle size can provide a suitable lithium ion embedding site. For spherical graphite negative electrode materials, if the particle size is small, it may lead to the decomposition of the electrolyte and the increase of side reactions. If the particle size is too large, the lithium ion embedding sites are small. Too large or too small particle size will affect the overall efficiency of the battery. A suitable specific surface area can provide more active sites for the adsorption and desorption of lithium ions, thereby increasing the energy storage capacity of the battery, and can increase the contact area between the electrode and the electrolyte, thereby increasing the rate of the electrode reaction. However, an excessively high specific surface area may lead to an uneven distribution of lithium ions on the electrode surface and an increase in side reactions on the electrode surface, reducing the overall efficiency of the battery.
[0033] In some embodiments of the second object of the present invention, the interlayer spacing of the micro-expanded spherical graphite is 0.335-0.450nm, the tap density is ≥0.5g / ml, and the sulfur content is ≤50ppm. Sulfur element exists as an impurity and may form a variety of lithium sulfides in the electrochemical process. These lithium sulfides have poor electrochemical stability and are easily dissolved in the electrolyte, resulting in rapid decay of the battery capacity. At the same time, the presence of sulfur may promote the decomposition of the electrolyte and produce insoluble solid by-products. These by-products will be deposited on the electrode surface, increase the internal resistance of the battery, and reduce the battery performance. Controlling the sulfur content to ≤50ppm can further ensure the battery performance.
[0034] In the specific embodiment of the present application, the parameters involved are tested by the following test methods: Interlayer spacing test: The interlayer spacing of graphene is determined by analyzing the (002) peak in the X-ray diffraction pattern. XRD (X-ray Diffraction) can use a Japanese Rigaku Ultima IV tester, using a copper target, a scanning range of 5-90°, and a scanning speed of 10° / min as an X-ray excitation source to test the crystallinity of the sample.
[0035] Tap density test: The test method refers to GB / T 5162-2021.
[0036] Particle size test: The test method refers to GB / T 19077-2016.
[0037] Specific surface area test: Use JW-BK200B instrument for testing, the test conditions are: 250℃ / 2.5h treatment, use high-purity nitrogen for adsorption.
[0038] Sulfur content test: XPS test was used. XPS (X-ray electron energy spectrum analysis, X-ray photoelectron spectroscopy) used an XPS tester of model ESCA lab 250. The sample was in energy analysis mode with a base pressure of 3×10-8Pa and A1 Kα 1486.8eV X-rays were used as the excitation source to test the chemical composition of the sample.
[0039] Battery capacity test: Spherical graphite raw materials are prepared into button batteries, which are loaded on the Blue Electric test platform for 0.1C charge and discharge tests. The data are collated to obtain the battery capacity.
[0040] First-effect test: prepare button-type batteries from spherical graphite raw materials, load the batteries on the Blue Electric test platform, conduct 0.1C charge and discharge tests, and organize the data to obtain the first-effect data. Example 1
[0041] This embodiment provides a method for preparing micro-expanded layer spherical graphite: S1, acidification: 1 kg of spherical graphite and 42 kg of 98% sulfuric acid were stirred and mixed for 1 hour to obtain a mixed solution a; S2, hydrolysis: add 40kg water to the mixed solution a for hydrolysis reaction, the reaction time is 0.5h, and a mixed solution b is obtained; S3, filter pressing: the mixed solution b is filter pressed using 1 kg of ammonia water and 41 kg of water for 26 hours to obtain a solid spherical graphite intermediate c; S4, sintering: the solid spherical graphite intermediate c is dried, granulated in a granulator, and then placed in a 1250° C. carbonization furnace for carbonization treatment for 20 hours to obtain the target micro-expanded layer spherical graphite.
[0042] After testing, the interlayer spacing of spherical graphite raw materials is 0.332nm and the specific surface area is 5.6m 2 / g, D50 is 17.283μm, tap density is 0.9g / mL, S content is 20 ppm, and the spherical graphite raw material is prepared into a button battery. The test shows that its capacity is 369mAh / g and the first efficiency is 90%. The particle size test graph and SEM electron microscope graph of the spherical graphite raw material are shown as follows: Figure 1 , Figure 2 shown.
[0043] The interlayer spacing of the micro-expanded spherical graphite prepared in Example 1 is 0.338nm and the specific surface area is 5.8m 2 / g, D50 is 18.180μm, tap density is 0.8g / mL, S content is 35 ppm, and the micro-expanded spherical graphite raw material is prepared into a button battery. The test shows that its capacity is 369mAh / g and the first efficiency is 92%. The particle size test graph and SEM electron microscope graph of the spherical graphite raw material are shown in Figure 3 , Figure 4 As shown, from Figure 2 , Figure 4 It can be seen that the microscopic morphology of the micro-expanded layer spherical graphite obtained in Example 1 remains basically consistent. Example 2
[0044] Different from Example 1, in step S1, 1 kg of spherical graphite is stirred and mixed with 48 kg of 90% sulfuric acid for 1 hour; in step S4, the carbonization temperature is 1350°C and the carbonization time is 18 hours. The other steps are the same as in Example 1.
[0045] The interlayer spacing of the micro-expanded spherical graphite prepared in Example 2 is 0.335nm and the specific surface area is 5.8m 2 / g, D50 is 17.629μm, tap density is 0.8g / mL, S content is 33 ppm, and the micro-expanded spherical graphite raw material is prepared into a button battery. The test shows that its capacity is 368mAh / g and the first efficiency is 92%. Example 3
[0046] The difference from Example 1 is that in step S3, 50 kg of water and 7 kg of ammonia water are added to react for 20 hours, and filter pressing is performed to obtain a solid spherical graphite intermediate c; in step S4, the carbonization temperature is 1000°C and the carbonization time is 24 hours. The other steps are the same as in Example 1.
[0047] The interlayer spacing of the micro-expanded spherical graphite prepared in Example 3 is 0.337nm and the specific surface area is 5.8m 2 / g, D50 is 18.013μm, tap density is 0.8g / mL, S content is 30ppm, and the micro-expanded spherical graphite raw material is prepared into a button battery. The test shows that its capacity is 369mAh / g and the first efficiency is 92%. Comparative Example 1
[0048] S1, acidification: 1 kg of spherical graphite and 42 kg of 65% sulfuric acid were stirred and mixed for 1 hour to obtain a mixed solution a; S2, hydrolysis: add 40kg water to the mixed solution a for hydrolysis reaction, the reaction time is 0.5h, and a mixed solution b is obtained; S3, filter pressing: add 23 kg of water and 1 kg of ammonia water to the mixed solution b and react for 24 hours, and filter press to obtain a solid spherical graphite intermediate c; S4, sintering: the solid spherical graphite intermediate c is dried, granulated in a granulator, and then placed in a 1250° C. carbonization furnace for carbonization for 20 hours to obtain modified spherical graphite.
[0049] The interlayer spacing of the modified spherical graphite prepared in Comparative Example 1 is 0.332 nm and the specific surface area is 5.7 m 2 / g, D50 is 17.283μm, tap density is 0.8g / mL, S content is 30 ppm, the spherical graphite prepared in Comparative Example 1 is used as raw material to prepare button-type batteries, and the test shows that its capacity is 368mAh / g and the first efficiency is 89%. The particle size test graph and SEM electron microscope graph of the modified spherical graphite obtained in Comparative Example 1 are shown as follows: Figure 5 , Figure 6 Although the microscopic characteristics of the modified spherical graphite obtained in Comparative Example 1 are still basically consistent with the spherical graphite raw material, the first efficiency of the battery is not improved because the interlayer spacing is not opened. Comparative Example 2
[0050] S1. Oxidation: 1 kg of spherical graphite and 5.5 kg of 30% hydrogen peroxide were stirred for 1 hour to obtain a mixed solution a.
[0051] S2, hydrolysis: add 40kg water to the mixed solution a for hydrolysis reaction, the reaction time is 0.5h, and a mixed solution b is obtained; S3, filter pressing: add 23kg water and 1kg ammonia water to the mixed solution b and react for 24h, and filter pressing to obtain a solid spherical graphite intermediate c; 30 S4, sintering: the solid spherical graphite intermediate c is dried, granulated in a granulator, and then placed in a 1250° C. carbonization furnace for carbonization for 20 hours to obtain modified spherical graphite.
[0052] The interlayer spacing of the modified spherical graphite prepared in Comparative Example 2 is 0.332 nm and the specific surface area is 12.6 m 2 / g, D50 is 26.290μm, tap density is 0.3g / mL, S content is 20ppm, the spherical graphite raw material obtained in micro comparative example 1 is prepared into a button battery, and its capacity is 362mAh / g and the first efficiency is 86%. The particle size test graph and SEM electron microscope graph of the spherical graphite obtained in comparative example 2 are shown as follows: Figure 7 , Figure 8 As shown. Figure 2 , Figure 8 It can be seen that the modified spherical graphite obtained in Comparative Example 2 underwent obvious oxidation exfoliation, and its microscopic morphology was no longer close to the intrinsic morphology requirements of the raw material, but its interlayer spacing was not opened. This is because hydrogen peroxide itself cannot directly open the interlayer spacing of spherical graphite because it does not have enough energy to destroy the van der Waals force between the spherical graphite layers. Correspondingly, the electrical properties of this group of experiments also decreased based on the spherical graphite raw materials. Comparative Example 3
[0053] S1, acidification: 1 kg of spherical graphite and 42 kg of 98% sulfuric acid were stirred and mixed for 1 hour to obtain a mixed solution a; S2. Oxidation: Add 0.2 kg potassium permanganate and 0.8 kg water to the mixed solution b for oxidation reaction. The oxidation time is 1.5 h to obtain a mixed solution a2.
[0054] S3, hydrolysis: add 40kg water to the mixed solution a2 for hydrolysis reaction, the reaction time is 0.5h, and a mixed solution b is obtained; S4, filter pressing: add 23 kg of water and 1 kg of ammonia water to the mixed solution b and react for 24 hours, and filter press to obtain a solid spherical graphite intermediate c; S5. Sintering: The solid spherical graphite intermediate c is dried, granulated in a granulator, and then placed in a 1250° C. carbonization furnace for carbonization for 20 hours to obtain modified spherical graphite.
[0055] The interlayer spacing of the modified spherical graphite prepared in Comparative Example 3 is 0.457 nm and the specific surface area is 13.1 m 2 / g, D50 is 26.326μm, tap density is 0.1g / mL, S content is 40ppm, the spherical graphite raw material obtained in micro comparative example 1 is prepared into a button battery, and its capacity is 360mAh / g and the first efficiency is 84%. The particle size test graph and SEM electron microscope graph of the spherical graphite obtained in comparative example 2 are shown as follows: Fig. 9 , Fig.10 As shown. Figure 2 , Fig.10 It can be seen that the modified spherical graphite obtained in Comparative Example 3 has undergone obvious exfoliation, and its microscopic morphology is no longer close to the intrinsic morphology requirements of the raw material. Correspondingly, its electrical properties are also reduced based on the spherical graphite raw material.
[0056] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0057] The above is a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A method for preparing micro-expanded layer spherical graphite, characterized in that: The method comprises the following steps: acidifying, hydrolyzing, filtering and sintering the spherical graphite, wherein the interlayer spacing of the micro-expanded spherical graphite is greater than the interlayer spacing of the spherical graphite.
2. The method for preparing micro-expanded layer spherical graphite according to claim 1, characterized in that: The acidification comprises mixing spherical graphite with sulfuric acid, wherein the concentration of the sulfuric acid is ≥90%.
3. The method for preparing micro-expanded layer spherical graphite according to claim 2, characterized in that: The mass ratio of the spherical graphite to the sulfuric acid is 1:40-50.
4. The method for preparing micro-expanded layer spherical graphite according to claim 1, characterized in that: The hydrolysis comprises directly adding water to the acidified spherical graphite to replace the interlayer acid of the spherical graphite.
5. The method for preparing micro-expanded layer spherical graphite according to claim 1, characterized in that: The sintering is carbonization at 900-1400° C., and the carbonization time is 16-24 hours.
6. The method for preparing micro-expanded layer spherical graphite according to claim 2, characterized in that: The filter pressing comprises mixing the hydrolyzed spherical graphite with water and ammonia water for reaction, and filter pressing the spherical graphite into a solid state.
7. The method for preparing micro-expanded layer spherical graphite according to claim 6, characterized in that: The mass ratio of the ammonia water to the spherical graphite is 1:1-10; Preferably, the mass ratio of the spherical graphite to water in the filter press process is 1:40-50; Preferably, the reaction time of the filter press process is 20 to 28 hours.
8. A micro-expanded spherical graphite, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5, the micro-expanded spherical graphite layer spacing is 0.335-0.450nm, and the tap density is ≥0.5g / ml.
9. The micro-expanded layer spherical graphite according to claim 8, characterized in that: The particle size of the micro-expanded layer spherical graphite is 10-20 μm, and / or the specific surface area is 5-12 m 2 / g.
10. A micro-expanded spherical graphite, characterized in that: Prepared by the preparation method according to any one of claims 6 to 7, the interlayer spacing of the micro-expanded layer spherical graphite is 0.335-0.450nm, the tap density is ≥0.5g / ml, and the sulfur content is ≤50ppm.
Citation Information
Patent Citations
Preparation method of manganese oxide-small-size micro-expanded natural graphite used as lithium battery negative electrode material
CN109616668A
Spheroidal graphite material and preparation method and application thereof
CN113526501A
Nitrogen-doped expanded-layer graphite / tin phosphide multilayer composite material and preparation method thereof
CN114420936A
Method of producing intercalated graphite, intercalated graphite and flexible graphite sheet
RU2422406C1
Cited By
Amorphous conductive carbon skeleton for core-shell type silicon-carbon negative electrode material and preparation method of amorphous conductive carbon skeleton
CN120607253A
An amorphous conductive carbon framework for core-shell silicon-carbon negative electrode materials and a preparation method thereof
CN120607253B